Lumbar mobility in former elite male weight-lifters, soccer players, long-distance runners and shooters - Raty, H. P.; Battie, M. C.; Videman, T.; Sarna, S. (Clinical Biomechanics, 1997)
OBJECTIVE: To investigate the long-term effects of different loading conditions in sports and work on lumbar mobility. DESIGN: Factors associated with lumbar mobility were sought by examining sports experience, occupational history, back pain history, anthropometric characteristics, and lumbar magnetic resonance images in 114 former Finnish male elite athletes: 30 soccer players, 29 weight-lifters, 27 long-distance runners, and 28 shooters, aged 45-68 yr. BACKGROUND: Back pain and aging reduce spinal mobility, whereas some sports may increase it. Little is known about the effects of common loading conditions found in work and sports, that do not require extremes of spinal motion on lumbar mobility later in life. METHODS: Sports and occupational histories were obtained from a standardized interview. Lumbar mobility was measured by the flexicurve method. Disc degeneration was evaluated from lumbar magnetic resonance images. The results were analysed with analysis of variance and covariance and multiple regression models. RESULTS: The athlete groups did not differ significantly in lumbar sagittal mobility. Higher body-mass index was associated with less flexion, reduced disc height with less extension, as was a high lifetime number of low back pain episodes. Occupations characterized by varying work postures and light lifting were associated with greater mobility, and heavy work with lesser mobility. CONCLUSIONS: Participation in sports with clearly different loading patterns, that do not emphasize extremes of spinal range of motion, do not appear to lead to significant differences in back mobility in later adulthood, but occupational loading factors and disc height narrowing appear to influence spinal mobility.